#TITLE_ALTERNATIVE# - PRILLA SONA HERGITHA (NIM. 101 07 011); Pembimbing Tugas Akhir : Dr. Agus Yodi Gunawan, LAURA
Bando Model is one of dinamical model of traffic congestion. It assumes that vehicle’s acceleration depend on distance with the preceding vehicle. When small deviation is added in steady state flow of identical car spacing, the stability of the system depend on driver’s sensitivity, velocity function and distance with the preceding vehicle. In this final project, we analyzed Bando Model for two velocity functions. The evolution of traffic flow is also simulated.